Evaluasi Program Reward Ibadah Umrah di MI Madinatunnajah - Nenden Dalfa Zakiyah Saniyah; Hesti Kusumaningrum (Ad-DA'WAH, 2026)
This study aims to evaluate the Umrah Reward Program in enhancing teachers’ work motivation at MI Madinatunnajah using the Discrepancy Evaluation Model (DEM), covering design, installation, process, product, and cost-benefit aspects. A descriptive qualitative approach was employed through observation, interviews, and document analysis involving the principal, rewarded teachers, and non-rewarded teachers. Data were analyzed through reduction, display, and conclusion drawing. The findings indicate that the program has generally been implemented well and positively influences teachers’ motivation and performance. However, discrepancies remain in written guidelines, selection mechanisms, resource and financial management, and program socialization. The program contributes to strengthening spiritual motivation and teacher professionalism, supporting the development of Islamic educational management and da’wah values through performance-based appreciation.